On Solutions of Fractional-Order Gas Dynamics Equation by Effective Techniques - Naveed Iqbal; Ali Akgül; Rasool Shah; Abdul Bariq; M. Mossa Al-Sawalha; Akbar Ali (Journal of Function Spaces)
In this work, the novel iterative transformation technique and homotopy perturbation transformation technique are used to calculate the fractional-order gas dynamics equation. In this technique, the novel iteration method and homotopy perturbation method are combined with the Elzaki transformation. The current methods are implemented with four examples to show the efficacy and validation of the techniques. The approximate solutions obtained by the given techniques show that the methods are accurate and easy to apply to other linear and nonlinear problems.